Sistem Informasi Persediaan Barang Dengan Metode Economic Order Quantity Berbasis Web Pada PT. Hoseki Prima Indonesia - Iwan Mulyana; Abdul Rohim; Rahmawati (LPPM STMIK AL MUSLIM, 2023)
Inventory Information System is a system that can monitor the rate of entry and exit of goods at PT. Hoseki Prima Indonesia in the warehouse section where the circulation goes in and out goods in the company The problem that is often faced is the frequent occurrence of stock outs of goods, especially materials for the production process, so stop lines often occur, as well as finished goods that are often lost or the condition of the goods does not match the actual goods in the warehouse. With the existence of a web-based inventory information system, it can improve the quality of goods as well as monitor the circulation of goods in and out both ordered by customers or goods in the form of materials for the production process This inventory information system has deficiencies that can be upgraded from the application side, namely by collaborating or developing an Android-based system so that it can be utilized according to the needs of the times Keywords: Inventory Information System